PERAN DAN PELUANG SL-PHT KOMODITI LADA MEMPENGARUHI KOGNITIF PETANI PERKEBUNAN RAKYAT (Studi kasus: Propinsi Lampung) - ROOSGANDHA ELIZABETH; RACHMAT HENDAYANA (SOCA: Jurnal Sosial Ekonomi Pertanian, 2005)
IPM-FL (“SL-PHT”) contained more strategy alternatives and approach to develop IPM(Integrated Pest Management) in pepper agribusiness, to improve competitive trade andcommerce globalization demand like eco labeling qualification (quality improvement) andfree pesticide (safety) brand image. Many IPM curriculum supported by management of IPMFLwhich have been prepared previously, but in practiced, pepper farmers must conductedselective depend on they needed, that is: 1) pest evaluation method; 2) making ‘Bokashi’fertilize method; 3) specific location for repairing of fertilize dose; 4) the land preparation; 5)pepper cultivation method (planting, providing seed); 6) making of Trichoderma method.Pepper (Piper nigrum, L) is eldest product and traditional export commodity of spices whichhave strategic opportunities on estate agribusiness (ex. Lampung Black Pepper). However, inLampung Province, the based on income source from coffee and other plant like rubber,beside from pepper farming system;. Black pepper from Lampung different by the otherpepper only in the treatment after harvest that which dried directly without soaking andpeeling. All farmers In IPM-FL participant include try out farmer groups, pure farmer groupand followed farmer groups. More than 70% respondent expressed to feel knowledge afterfollowing IPM-FL.